Distribution and characterization of Lessepsian migrant fishes along the coast of Libya - E.A. Shakman; R. Kinzelbach (Acta Ichthyologica et Piscatoria, 2007)
Background. The Lessepsian migrant ichthyofauna along the approximately 2000 km of the Libyan coastline has been poorly known. A comprehensive study, addressing this issue, was needed and therefore the presently reported research project is intended to close the gap, through identifying the fish species and assessing their distribution. Materials and methods. The catches of commercial fisheries vessels were monitored and examined in a standardized procedure between January 2005 and March 2006. The project covered a total of 4273 specimens, comprising 1901 specimens of Siganus luridus, 1885 specimens of Siganus rivulatus, and 487 specimens of fourteen other Lessepsian fish species. Results. Sixteen Lessepsian fish species, representing 14 families, were recently found along the Libyan coast, two of which are considered to be first records for Libya: Herklotsichthys punctatus (Rüppell, 1837) and Liza carinata (Valenciennes, 1836). Approximately 50% of the immigrants were found along the entire stretch of the Libyan coast, 12.5% in the east and central regions, and 37.5% were restricted to the eastern part of the Libyan coast. All were found in the coastal area (1-50 m depth), 12.5% on the vegetation, 31.25% on sandy bottoms, 12.5% on rocks, while the majority of them (43.75%) were pelagic. Regarding the size, 75% were medium, 18.75% large, and 6.25% were categorized as small. Conclusion. The north African coast (west of the Nile delta)-compared with the Levantine- and Anatolian coast of the Mediterranean Sea-was considered to be settled by immigrants from the Red Sea with some delay, due to sea currents. If so, this situation has changed meanwhile at least for fishes. More than 37% of the recorded Lessepsian fish species are of commercial value, especially rabbitfish (Siganus spp.). The future research should be focussed on monitoring the stocks, especially of the commercially valuable species, regarding the biology and ecology of the Lessepsian migrants. Also, possible further additions to the fish fauna, by new invaders, should be recorded.